A content analysis of the opinion columns of Luis D. Beltran and Terodoro F. Valencia during the first one hundred days of the Aquino government - Arboleda, Rainelda Jiffin I.
This study is a content analysis of the opinion columns of Luis D. Beltran and Teodoro Valencia ("Straight from the Shoulder" and "Over a Cup of Coffee" respectively) during the first one hundred days of the government of President Corazon C. Aquino. These first one hundred days is commonly called a 'honeymoon' where the press-government relationship is concerned, since journalists usually refrain from writing critically about the President so as to give him/her breathing space and time to get used to his/her new responsibilities.